Thinking Styles and University Self-Efficacy Among Deaf, Hard-of-Hearing, and Hearing Students. (13th August 2015) - Cheng, Sanyin; Zhang, Li-Fang; Hu, Xiaozhong
Abstract : This study explores how students' thinking styles are related to their university self-efficacy, by administering the Thinking Styles Inventory-Revised II and the University Self-Efficacy Scale to 366 deaf or hard-of-hearing (DHH) and 467 hearing university students in mainland China. Results showed that, among all participants, those with Type I styles (i.e., more creativity-generating, less structured, and cognitively more complex) had higher levels of university self-efficacy. At the same time, DHH students with Type II styles (i.e., more norm-favoring, more structured, and cognitively more simplistic) had lower levels of university self-efficacy. The contributions, limitations, and implications of the present research are discussed.